Effect of the Pseudogap on the Quasiparticle Transport from the Static Limit to Finite Energy for Cuprate Superconductors. Issue 11 (7th October 2018) - Zhao, Huaisong; Yan, Xu; Wan, Yong; Yuan, Feng
Abstract: Within the renormalized t ‐ J model and self‐consistent mean field theory, the doping and energy dependences of the quasiparticle transport is studied in cuprate superconductors, especially in the underdoped region. By calculating the doping and energy dependence of the ratio of the thermal conductivity to the electrical conductivity at temperature T, κ ( ω ) / σ ( ω ) T (the form of the Wiedemann–Franz law), it is shown that κ ( ω ) / σ ( ω ) T increases with the increase of energy from underdoping to overdoping, whereas it is constant in heavily overdoped cuprate superconductors and recovers the result of the Wiedemann–Franz law at zero energy. The slope of κ ( ω ) / σ ( ω ) T is the highest in the underdoped region, decreases with increasing the doping concentration in the whole doping range, and reaches zero in the heavily overdoped region. In particular, the ratio κ ( ω ) / σ ( ω ) T as a function of energy exhibits a characteristic peak over the transition from underdoping to overdoping, and the position of the characteristic peak ωWF decreases monotonically upon increasing doping concentration. Therefore, these results indicate that the slope of κ ( ω ) / σ ( ω ) T and characteristic peaks as a function of doping are related to the appearance of the pseudogap in cuprate superconductors. Abstract : The pseudogap effect on quasiparticle transport in cuprate superconductors is studied based on the renormalized t ‐ J model. At the static limit, the cuprate superconductors deviate from the Wiedemann–Franz (WF) law because of the pseudogap and recover the WF law in the heavily overdoped case. Meanwhile, at finite energy, a characteristic peak scales with the effective pseudogap.